Effect of compositional dependence on physicochemical properties of Bi2Se3 doped system. (September 2016) - Adam, A.M.; Lilov, E.; Petkov, P.
Abstract: Crystalline bulk compositions of Bi2 (Se1−x Tex )3 system with ( x=0.0–1.00) were prepared using the conventional melting method. The structural properties of bulk samples were studied with the aid of XRD and SEM analysis. Compositional element distribution and elemental ratios were estimated with EDX spectroscopy that attached with SEM. XRD patterns show that the prepared compounds are crystalline materials with single phases of Bi2 Se3 and Bi2 Te3 and/or a ternary phase. The grain size calculations were performed using the well-known Scherrer equation. The thermal studies analysis was carried out by using DSC. DSC studies revealed that the prepared samples are stable and none decomposable over the temperature range. Physicochemical properties such as compactness, molar volume and the free volume percentage were calculated for the concerned alloys based on the experimentally calculated densities of each compound. The measured parameters showed a strong dependence on the Te content.